Professional mobility as one of the criteria for the effectiveness of professional development - Іншаков, Артур (Pedagogy of Higher and Secondary Education, 2015)
Gribovа L. V. Professional mobility as one of the criteria for the effectiveness of professional development. In the article, based upon theoretical apprehension of various scientific approaches the methodological conditions of trends in development of specialists’ professional mobility in the context of market economy, unstable social and political situation in Ukraine have been determined. Also some economic, psychological and social motives of facilitating professional mobility during qualification improvement courses have been defined.